Characterization of Cellulose Acetate Membrane from Nutmeg Shells - Bhayu Gita Bhernama; Nurhayati; Surya Adi Saputra; Jihan Amalia (JURNAL SAINS NATURAL, 2023)
The membrane is a semipermeable selective thin layer that is used as a barrier between two phases, the feed phase and the permeate phase. Several studies have been carried out on the synthesis of cellulose acetate membranes, but research on cellulose acetate membranes from nutmeg shell waste is still rare. Therefore, the characterization of cellulose acetate membrane from a nutmeg shell was conducted. This study aims to characterize cellulose acetate membranes from nutmeg shells using the phase inversion method with variations in the weight of cellulose acetate 0.1 and 0.2 grams. The plasticizers used are polyvinyl chloride (PVC) and dope solution. Characterization was carried out in thickness, tensile strength, morphology by Scanning Electron Microscope (SEM), functional groups, membrane permeability, rejection value, degree of swelling, and membrane standards. The results obtained for good morphological characterization were found in membranes number 2 and 4, the value of rejection and flux on membrane number 2 (t = 1 minute) was 31.1%, and the flux value was 4.6 L/m2.h for membrane number 3 (t) (t = 3 minutes) 31.6% and the flux value was 0.3 L/m2 per hour. The good thickness and strength of the membrane are found in the number 1 membrane, with a thickness of 0.11 mm and tensile strength of 3.06 MPa. Swelling degree and suitable membranes are found in membrane number 1, 59.52%, and 32.2%, respectively. The functional groups contained in the FTIR spectrum include the C – H group, which is located in the wave number range of 2959.79 cm-1, C = O is located at 1722.06 cm-1, C –O acetyl is located at 1271.04 cm-1 and C – O stretching is located at 1072.13 cm-1, and the presence of a PVC group is located at 742.12 cm-1. The conclusion is that membrane number 1 is good for further application.